FACTORS INFLUENCING PARENTS’ INABILITY TO MEET CHILDREN’S BASIC NEEDS IN KWARA CENTRAL NIGERIA - Rasheed, Shofiu Adewuyi; Abdulaziz, Isiaka (African Journal of Social and Behavioural Sciences, 2025)
This study aimed to identify the factors influencing parents' ability to meet the physiological needs of their children in Kwara Central, Nigeria. The target population included parents from diverse socioeconomic backgrounds, including those with varying levels of education, income, and housing quality. Kwara Central was divided into four local government areas, and 100 respondents were randomly selected from each area, ensuring representation of different social strata. A descriptive survey research design was used for the study. The use of a descriptive survey design allowed for the collection of comprehensive data from a diverse group of parents, ensuring that the findings were both reliable and representative. The statistical analysis, including mean scores and t-tests, provided a clear understanding of the relationships between socioeconomic factors and parents' ability to meet their children's needs, confirming the validity of the conclusions drawn from the study. The researcher designed a 20-item structured questionnaire to collect data on socioeconomic factors affecting parents’ ability to meet their children's physiological needs. The questionnaire gathered information on parental education, income, and housing quality. Data were analysed using mean scores and t-tests at a 0.05 level of significance to determine the influence of these factors. The findings showed that while parents' educational background did not significantly impact their ability to meet their children's physiological needs, income and housing quality were influential. Specifically, higher income levels and better housing conditions enabled parents to better provide for their children's basic needs. Based on these results, the study recommended that parents seek to improve their income sources to support their families better. It also suggested that the government should increase wages to help workers build wealth and create policies to support low-income earners in obtaining adequate housing.